PENGARUH PROFITABILITAS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK - Vicka Stawati (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2020)
The purpose of this study was to examine the effect of Profitability, Leverage and Size Company on Tax Avoidance. The population which is the object of this research is argicultural sectors listed on Indonesia Stock Exchange (BEI) in 2014 - 2018. The total population of 20 companies, this study obtained by purposive sampling technique which then resulted in 6 research samples for further investigation. The analysis technique used is multiple regression analysis. Based on data analysis and discussion can be concluded that Profitability, Leverage, and Company Size has effect on Tax Avoidance. This means that the government has not succeeded in conducting Tax Amnesty program which has the impact of the company will do Tax Avoidance.